Divergent paths of mammary gland involution: unveiling the cellular dynamics in abruptly and gradually involuted mouse models - Sarmila Majumder; Sanjay Mishra; Neelam Shinde; Maria C. Cuitino; Morgan Bauer; Dinesh Ahirwar; Mustafa M. Basree; Vijaya Bharti; Kate Ormiston; Resham Mawalkar; Sara Alsammerai; Gautam Sarathy; et al. (Breast Cancer Research)
Abstract Background Epidemiological studies associate an increase in breast cancer risk, particularly triple-negative breast cancer (TNBC), with lack of breastfeeding. This is more prevalent in African American women, with significantly lower rate of breastfeeding compared to Caucasian women. Prolonged breastfeeding leads to gradual involution (GI), whereas short-term or lack of breastfeeding leads to abrupt involution (AI) of the breast. Our previous study utilizing a murine model demonstrated precancerous changes, specifically hyperplasia, a non-obligate precursor of breast cancer in the mammary glands of AI mice. Here we investigated mechanisms during early events of AI that prompts precancerous changes in mouse mammary glands. Methods Uniparous FVB/N mice were randomized to AI and GI on postpartum day 7 when all pups were removed from AI dams. GI dams were allowed to nurse the pups till day 31. Cell death kinetics and gene expression were assessed by TUNEL assay and qPCR respectively. Immune cell changes were investigated by flow cytometry, cytokine array and multiplex immunofluorescence. 3D-organoid cultures were used for in vitro assay of luminal progenitor cells. Results AI results in rapid cell death, DNA repair response, and immunosuppressive myeloid cells infiltration, leading to a chronically inflamed microenvironment. GI elicits a more controlled immune response and extended cell death. At the peak of cell death, AI glands harbored more immunosuppressive myeloid-derived suppressor cells (MDSCs) and CD206 + M2-like macrophages, known to promote oncogenic events, compared to GI glands. AI glands exhibit an enrichment of CCL9-producing MDSCs and CD206 + M2-like macrophages that promote expansion of ELF5 + /ERα- luminal cells, both in vitro and in vivo. Multiplex imaging of AI glands demonstrated an increase in ELF5 + /WNT5a + luminal cells alongside a reduction in the ELF5 + /ERα + population when involution appeared histologically complete. A significantly higher number of CD206 + cells in post involution AI gland attests to a chronically inflamed state induced by AI. Conclusions Our findings reveal significant disparities between AI and GI gland dynamics at the early phase of involution. CCL9, secreted by immune cells at the peak of cell death promotes expansion of Elf5 + /ERα- luminal progenitor cells, the putative precursors of TNBC connecting early events of AI with increased breast cancer risk.